Perancangan Routing OSPF Mikrotik pada PT. Arsen Kusuma Indonesia - Kurniawan, Oky; Taufik, Andi; Ariani, Fattya (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The advancement of internet connectivity in Indonesia has had a significant impact on both individuals and businesses. The need for real-time information is crucial, and to obtain it quickly, even instantly, it requires a fast and stable internet connection. Therefore, in order to provide a stable internet service and avoid total downtime in the backbone network between routers, internet service providers typically have two or more links in their backbone network, with one of them designated as a secondary or backup link in case the primary link experiences disruption. The process of switching from the primary link to the backup link is called failover or redundant linking. Many failover systems are implemented in internet service provider networks, one of which uses dynamic routing technologies like OSPF (Open Shortest Path First). Routing is the process of transferring data from one network to another. With dynamic routing, the routing mechanism operates dynamically by quickly and accurately determining the shortest path between the sender and receiver devices. OSPF is a dynamic routing protocol that uses a link-state algorithm to build and calculate the shortest paths to all known destinations